Pengaruh Volunteer Gerakan SUMUT Mengajar Terhadap Kesiapan Menjadi Calon Pendidik PAI Kab. Langkat - Widya, Nabila; Albina, Meyniar (Jayapangus Press, 2025)
Volunteering serves as an important avenue for university students, particularly prospective teachers, to develop soft skills, broaden social experiences, and enhance their readiness for the workforce. This study aims to examine the influence of participation in volunteering activities, specifically through Gerakan Sumut Mengajar (GSM), on the readiness of prospective Islamic Religious Education (PAI) teachers. The research employed a quantitative method with a correlational approach. The sample consisted of 100 respondents who were GSM alumni, selected through purposive sampling. Data were collected using questionnaires and analyzed through correlation tests, simple linear regression, and the coefficient of determination. The findings indicate a significant relationship between volunteering and teacher readiness, with a correlation value of r = 0.656. The coefficient of determination analysis shows that GSM volunteering contributes 43.1% to the readiness of prospective PAI teachers. These results highlight that volunteering experiences play a positive role in fostering the professional, social, and personal readiness of future educators, making it a valuable complement to field practice programs in higher education.